Book review: Kinship care: Fostering effective family and friends placements. Elaine Farmer and Sue Moyers London, Jessica Kingsley Publications, 2008. 254pp, ISBN 978 1 84310 631 9 - Leon Fulcher (Scottish Journal of Residential Child Care)
Family and kinship care has a long history. It dates from times when children or young people were taken in to extended family networks or placed with relatives when birth parents or primary carers were unable, for whatever reasons, to provide them a home and developmental opportunities. Indigenous cultures – such as found amongst Maori peoples in New Zealand – commonly arranged for the eldest child to be placed with an elder aunt, uncle or grandparent who thus passed on important cultural learning and practices to the next generation. In South Africa, family and kinship care innovations are being used to support family groups where parents or primary carers have died because of HIV-AIDS. Family and kinship care has always played a significant part in child welfare systems operating everywhere.